2014
DOI: 10.2166/wst.2014.096
|View full text |Cite
|
Sign up to set email alerts
|

Light attenuation – a more effective basis for the management of fine suspended sediment than mass concentration?

Abstract: Fine sediment continues to be a major diffuse pollution concern with its multiple effects on aquatic ecosystems. Mass concentrations (and loads) of fine sediment are usually measured and modelled, apparently with the assumption that environmental effects of sediment are predictable from mass concentrations. However, some severe impacts of fine sediment may not correlate well with mass concentration, notably those related to light attenuation by suspended particles. Light attenuation per unit mass concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 0 publications
3
22
1
Order By: Relevance
“…Across all sites, visual clarity is strongly correlated with TSS and turbidity as has been reported by Davies-Colley et al (2014). However, while the R 2 values are relatively high, SE values are also high, suggesting that the relationships are not very precisely predictive.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Across all sites, visual clarity is strongly correlated with TSS and turbidity as has been reported by Davies-Colley et al (2014). However, while the R 2 values are relatively high, SE values are also high, suggesting that the relationships are not very precisely predictive.…”
Section: Discussionsupporting
confidence: 67%
“…Clarity and turbidity were strongly (negatively) inter-related, though TSS is slightly less strongly related to both clarity and turbidity. Davies-Colley et al (2014) have presented mutual scatterplots for each combination of TSS, turbidity and visual clarity across all sites; a scatterplot of TSS and visual clarity shows that, while the correlation is strong, there is still appreciable data scatter (Fig. 1).…”
Section: Sediment and Related Optical Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…2 is defined for the photopic range of normal human vision; individuals who are color blind will have different sensitivities (Zaneveld and Pegau ). Despite the theoretical and practical advantages of measuring water clarity by the horizontal black disk (Davies‐Colley ), especially when light attenuation by fine sediment is of concern (Davies‐Colley et al ), the method has not been widely used outside of New Zealand, perhaps because of lack of awareness of the method, a scarcity of comparative studies, or perceptions that the black disk is affected by biases similar to the those of the Secchi disk.…”
Section: Measuring Optical Water Qualitymentioning
confidence: 99%
“…The few investigations associating BDV with turbidity and/or suspended solids concentrations have been specific to a single site (Steel and Neuhausser ), base flow conditions (Davies‐Colley and Close ), routine monthly monitoring data (Davies‐Colley et al ), or across long‐term median values over many sites (Smith et al ). However, Hughes et al () have reported preliminary results from their study comparing OWQ parameters during storm flow.…”
Section: Measuring Optical Water Qualitymentioning
confidence: 99%